Maternal and perinatal outcomes of an alongside hospital Birth Center in the city of São Paulo, Brazil - Lobo, Sheila Fagundes; Oliveira, Sonia Maria Junqueira Vasconcellos de; Schneck, Camilla Alexsandra; Silva, Flora Maria Barbosa da; Bonadio, Isabel Cristina; Riesco, Maria Luiza Gonzalez (Revista da Escola de Enfermagem da USP, 2010)
The aim of this study was to describe the maternal and perinatal results of care in the alongside hospital birth center Casa de Maria (CPN-CM), located in the city of São Paulo. The random sample included 991 women and their newborns, attended between 2003 and 2006. The results showed that 92.2% of women had a companion of her choice during childbirth and the practices commonly used were shower or immersion bath (92.9%), amniotomy (62.6%), walking (47.6%), massage comfort (29.8%) and episiotomy (25.7%). Regarding newborns, 99.9% of them had Apgar scores =7 in the fifth minute, 9.3% received aspiration of the upper airway, no one needed to be intubated and 1.4% were removed to the hospital. The model of care in the CPN-CM provides maternal and perinatal outcomes expected for low obstetric risk women, and means a safe option and less interventionist model in normal childbirth.